Răspuns :
a) a² - 4b²= (a-2b)(a+ 2b)
b) 9y² - 0,25x²= ( 3y - 0,5x)( 3y + 0,5x)
c) 3a² - 8y² = (√3a - 2√2y )( √3a + 2√2y )
d) b² /6 - 1 /7x² = ( b/√6- x/√7)(b/√6 + x/√7 )
b) 9y² - 0,25x²= ( 3y - 0,5x)( 3y + 0,5x)
c) 3a² - 8y² = (√3a - 2√2y )( √3a + 2√2y )
d) b² /6 - 1 /7x² = ( b/√6- x/√7)(b/√6 + x/√7 )
a) (a-2b)(a+2b)
b) (3y-0,5x)(3y+0,5x)
c) (radical din 3a-radical din 8y)(radical din 3a+radical din 8y)
d) nu o stiu....
b) (3y-0,5x)(3y+0,5x)
c) (radical din 3a-radical din 8y)(radical din 3a+radical din 8y)
d) nu o stiu....